Threshold for diagnosing hypertension by automated office blood pressure using random sample population data - Wohlfahrt, Peter; Cífková, Renata; Movsisyan, Narine; Kunzová, Šárka; Lešovský, Jiří; Homolka, Martin; Soška, Vladimír; Bauerová, Hana; Lopez-Jimenez, Francisco; Sochor, Ondřej (Journal of hypertension, 2016)
OBJECTIVE: Manual office blood pressure (BP) is still recommended for diagnosing hypertension. However, its predictive value is decreased by errors in measurement technique and the white-coat effect. The errors can be eliminated by automated office BP (AOBP) measurement taking multiple readings with the participant resting quietly alone. Therefore, use of AOBP in clinical practice requires a threshold value for hypertension diagnosis. The aim of the present study was to determine an AOBP threshold corresponding to the 140/90 mmHg manual office BP using data from a large random population sample. METHODS: In 2145 participants (mean age 47.3 ± 11.3 years) randomly selected from a Brno population aged 25-64 years, BP was measured using manual mercury and automated office sphygmomanometers. RESULTS: Manual SBP (mean difference 6.39 ± 9.76 mmHg) and DBP (mean difference 2.50 ± 6.54 mmHg) were higher than the automated BP. According to polynomial regression, automated systole of 131.06 (95% confidence interval 130.43-131.70) and diastole of 85.43 (95% confidence interval 85.03-85.82) corresponded to the manual BP of 140/90 mmHg. Using this cut-off, the white-coat hypertension was present in 24% of participants with elevated manual BP, whereas 10% had masked hypertension and 11% masked uncontrolled hypertension. In individuals with masked uncontrolled hypertension, only AOBP was associated with the urinary albumin-creatinine ratio, whereas there was no association with manual BP. CONCLUSION: AOBP of 131/85 mmHg corresponds to the manual BP of 140/90 mmHg. This value may be used as a threshold for diagnosing hypertension using AOBP. However, outcome-driven studies are required to confirm this threshold.
Keywords: syndrom bílého pláště; dospělí; sfygmomanometry; hypertenze; Female; White Coat Hypertension; Adult; ženské pohlaví; Predictive Value of Tests; prediktivní hodnota testů; lidé; maskovaná hypertenze; referenční hodnoty; Algorithms; krevní tlak; Sphygmomanometers; Masked Hypertension; Hypertension; Male; Reference Values; Blood Pressure Determination; algoritmy; měření krevního tlaku; lidé středního věku; mužské pohlaví; Blood Pressure; Middle Aged; Humans